2019
DOI: 10.1002/pros.23879
|View full text |Cite
|
Sign up to set email alerts
|

T‐type calcium channels drive the proliferation of androgen‐receptor negative prostate cancer cells

Abstract: Background Androgen deprivation therapy (ADT) is the treatment of choice for metastatic prostate cancer (PCa). After an initial response to ADT, PCa cells can generate castration resistant (CRPC) or neuroendocrine (NEPC) malignancies, which are incurable. T‐type calcium channels (TTCCs) are emerging as promising therapeutic targets for several cancers, but their role in PCa progression has never been investigated. Methods To examine the role of TTCCs in PCa, we analyzed their expression level, copy number vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…TTCCs have been shown to be involved in embryonic development and progression of several malignancies [142]. Recently, Silvestri et al, reported the overexpression of TTCCs isoform calcium voltage-gated channel subunit alpha1 G (CACNA1G) in advanced PCa that correlates with ADT resistance and poor prognosis while TTCC inhibition resulted in reduced PC3 cell proliferation and survival [143]. Previously, Gackiere and colleagues showed that another TTCC, CaV3.2 was highly expressed in NE cells derived from LNCaP cells.…”
Section: Neuroendocrine Trans-differentiation (Ned)mentioning
confidence: 99%
“…TTCCs have been shown to be involved in embryonic development and progression of several malignancies [142]. Recently, Silvestri et al, reported the overexpression of TTCCs isoform calcium voltage-gated channel subunit alpha1 G (CACNA1G) in advanced PCa that correlates with ADT resistance and poor prognosis while TTCC inhibition resulted in reduced PC3 cell proliferation and survival [143]. Previously, Gackiere and colleagues showed that another TTCC, CaV3.2 was highly expressed in NE cells derived from LNCaP cells.…”
Section: Neuroendocrine Trans-differentiation (Ned)mentioning
confidence: 99%
“…Overexpression of voltage-operated calcium channel T-type calcium channels (TTCCs) has also been observed in PCa with androgen receptor mutations [59]. Moreover, it has been shown that pharmacological or silencing inhibition of TTCCs causes a decrease in PCa cell proliferation and survival [59]. Based on these observations, it has been proposed that TTCCs control the proliferation of androgen-receptor negative PCa cells [59].…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Moreover, it has been shown that pharmacological or silencing inhibition of TTCCs causes a decrease in PCa cell proliferation and survival [59]. Based on these observations, it has been proposed that TTCCs control the proliferation of androgen-receptor negative PCa cells [59]. It has also been suggested that an androgen refractory state in which androgen receptor signaling is disrupted causes overexpression of TTCCs and increased cytosolic calcium in PCa cells [16].…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Similarly, T-type calcium channels were revealed to be a promising target for different cancers, particularly PCa, in light of their role in tumor growth. SiRNA-based inhibition of these particular calcium channels was able to lessen PC-3 cell survival and proliferation [40]. Transient receptor potential melastatin 2 is another calcium-permeable ion channel and considered as a prognostic marker for PCa [41].…”
Section: Sirna-mediated Cancer-associated Gene Silencing In Prostate Cancermentioning
confidence: 99%
“…T-type calcium channels Lessens cell survival and proliferation of PC-3 cells. [40] Transient receptor potential melastatin 2 (TRPM2) Induces autophagy in PC-3 cells.…”
Section: Dual Specificity Protein Kinase Ttkmentioning
confidence: 99%